PENGARUH LATIHAN MENENDANG LIMA BOLA KE GAWANG TERHADAP KETERAMPILAN KETEPATAN SHOOTING PEMAIN SSB BINA BAKAT U12 PEKANBARU - Zulhamsyah Zulhamsyah; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this research is that the accuracy of shooting of SSB Bina Bakat U-12 Pekanbaru is still lacking, it is seen from various test and official match and this is one factor causing the defeat. This type of research is a type of experimental research to see the effect of the form of exercise. The purpose of this study is to see the effect of training kick Five ball kegawang against the shooting accuracy of SSB Bina Bakat U-12 Pekanbaru. The population in this study is the team SSB Bina Bakat U-12 Pekanbaru amounting to 16 people. Sampling technique is by using total sampling, where the total population is sampled. The data retrieval technique is obtained from pre-test and post test. Instrument in this research use Test shooting at the ball as a tool to measure shooting accuracy skill. The analysis was performed using the t-test. based on data analysis and discussion, it can be concluded that there is a significant influence of training kick Nine ball kegawang against the skills of precision shooting players SSB Bina Bakat U-12 Pekanbaru proven with Thitung of 5,905 and Ttabel 1.753. Means Thitung> Tables. At ɑ = 0,05 level.Key Words: training kick five balls, precision shooting